CONTROLE BIOLÓGICO DA PODRIDÃO-RADICULAR-SECA DO FEIJOEIRO POR ISOLADOS DE TRICHODERMA spp - COSTA, Brenda Fernandes; PESSÔA, Guilherme Martins; MIRANDA, Hevelâyne Cristina Ferreira; SANTOS, Stephany; BLANCO, Neder Henrique Martinez; GRAICHEN, Felipe André Sganzerla (ANAIS DO ENIC, 2020)
-